Dr The KRG’s Inability Factors for Independently Exporting Oil: After 2023 - Shallaw Abdulkhaleq Mohammed; Ramyar Rashid Ahmed (Zanco Journal of Humanity Sciences)
This research investigates the factors hindering the Kurdistan Regional Government's (KRG) ability to independently export oil after 2023. The study examines the KRG's longstanding pursuit of self-determination and its hydrocarbon (oil and gas) resource management rights under the 2005 Iraqi constitution. It highlights the shift from a reliance on "hard power" tactics towards "soft power" strategies focused on economic development, revenue generation, and political autonomy. The abundant oil and gas reserves in the Kurdistan Region have played a pivotal role in shaping the KRG's primary policy, acting as a catalyst for regional growth and consolidation.